ADULTS READING ALOUD: A SURVEY OF CONTEMPORARY PRACTICES IN BRITAIN. Issue 1 (2nd January 2020) - Duncan, Sam; Freeman, Mark
ABSTRACT: While much is written about reading aloud to children, and as a teaching tool, far less is known about the oral reading that adults do at home, at work or in the community. This article presents the results of a national survey into whether, what, how and why adults across Britain may read aloud rather than in silence. Analysing data from 529 questionnaire responses, the article examines the frequency with which different text types are read aloud, the formations in which this is done – alone, with one other person or in a group – and the purposes of reading aloud and being read to, with attention to differences according to gender and age. Findings suggest that reading aloud happens in a number of different ways and for different purposes, across contexts and life domains, and that it has a significant relationship with aspects of the lifecourse and with identity formation and performance.